War and ethics a new just war theory - Fotion, Nicholas (Think now, 2007)
The US-led invasion of Iraq in 2003 prompted unprecedented public interest in the ethics of war, a debate that has raged furiously in the media, in politics and in the public consciousness ever since. In this fascinating and informative book, Nicholas Fotion, an expert on the ethics of military action, explores the notion of developing an ethical theory that guides the behaviour of those who are at war. Fotion gives a clear account of just war theory, presenting it as a useful device in helping us make decisions about what we should do when war appears on the horizon. Examining conflicts such as Korea, Vietnam, Iraq, Israel, the Falklands and Afghanistan, the book interrogates the roles of the various parties involved in military action - the military, government officials, and the side-line judges (journalists, citizens, scholars, neutral nations) - and the role just war theory should play as a direct guide to behaviour.